Factors Influencing the Success of Using Nasal Continuous Positive Airway Pressure in Neonates 28-34 Weeks' Gestation with Respiratory Distress Syndrome - Darnifayanti Darnifayanti; Fiva A Kadi; Aris Primadi; Tetty Yuniati; Sjarief Hidajat; Abdurachman Sukadi (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Premature babies are a serious problem worldwide, with 15 million births annually and more than one million dying from premature complications. Respiratory distress syndrome (RDS) is the most common cause of morbidity and mortality in neonates (44%), almost >70% require a breathing apparatus. Nasal Continuous positive airway pressure (NCPAP) is the recommended breathing apparatus for the management of RDS, but not all of them are successfully treated with NCPAP. This study aims to determine the factors that influence the success of using NCPAP in infants aged 28-34 weeks with RDS. This study is an analytical observational study with a prospective design in infants born at Hasan Sadikin Hospital Bandung in August to November 2018 with a gestational age of 28-34 weeks and experiencing RDS. Subjects who met the inclusion and exclusion criteria had NCPAP installed and evaluated. A total of 83 research subjects found the NCPAP success rate was 45.8%. Respiratory distress syndrome was more common in male infants 57.8%. Maximum baby weight 1500 grams53(63.9%), mean gestational age 32 weeks. Gestational age, antenatal steroid administration and grade of RDS based on chest X-ray were factors that significantly influenced the success of using NCPAP (p<0.05). After controlling for gestational age, administration of antenatal steroids and the degree of RDS, there was a significant relationship between the success of NCPAP and the administration of antenatal steroids ORadj 4.67 (p=0.043) and the degree of RDS with the success of NCPAP ORadj 21.25 (p=0.001). The degree of RDS based on chest X-ray and antenatal steroid administration were factors that significantly affected the success of NCPAP.